2013
DOI: 10.1002/rnc.2967
|View full text |Cite
|
Sign up to set email alerts
|

Distance-based undirected formations of single-integrator and double-integrator modeled agents in n -dimensional space

Abstract: SUMMARYWe study the local asymptotic stability of undirected formations of single‐integrator and double‐integrator modeled agents based on interagent distance control. First, we show that n‐dimensional undirected formations of single‐integrator modeled agents are locally asymptotically stable under a gradient control law. The stability analysis in this paper reveals that the local asymptotic stability does not require the infinitesimal rigidity of the formations. Second, on the basis of the topological equival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
124
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 187 publications
(126 citation statements)
references
References 13 publications
0
124
0
2
Order By: Relevance
“…There are a couple of works that have extended the analysis to three-or higher dimensional cases. Oh and Ahn (2014a) have designed a control law for distance-based undirected formations in n-dimension; but it has been focused on local stability properties. Park, Jeong, and Ahn (2013) have extended the existing result on distance-based formation control of three-agents in twodimension to four-agent tetrahedral formation with equilateral edges in three-dimension.…”
Section: Other Results In Distance-based Formation Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…There are a couple of works that have extended the analysis to three-or higher dimensional cases. Oh and Ahn (2014a) have designed a control law for distance-based undirected formations in n-dimension; but it has been focused on local stability properties. Park, Jeong, and Ahn (2013) have extended the existing result on distance-based formation control of three-agents in twodimension to four-agent tetrahedral formation with equilateral edges in three-dimension.…”
Section: Other Results In Distance-based Formation Controlmentioning
confidence: 99%
“…Further they have shown that the gradient control law is indeed the optimal control law with respect to a cost functional. Extending the result in Dörfler and Francis (2009) to n-dimension, Oh and Ahn (2014a) have shown that the infinitesimal rigidity of (G, p * ) is not crucial for local asymptotic stability of E p * . They have shown that if (G, p * ) is rigid in R n , E p * is locally asymptotically stable with respect to (32) by (1970).…”
Section: Single-integrator Casementioning
confidence: 96%
See 2 more Smart Citations
“…Recently, there have been wide research interests on the formation control problems [1][2][3][4][5][6][7][8][9][10]. Basically, the for mation control problem arises when we deal with a group of agents that can move on in the plane or space.…”
Section: Introductionmentioning
confidence: 99%